Prevalence and factors associated with exposure to second-hand smoke (SHS) among young people: a cross-sectional study from The Gambia - Jallow, Isatou K.; Britton, John; Langley, Tessa (BMJ Publishing Group Ltd, 2018)
Background: Annually 600,000 deaths are attributed to exposure of non-smokers to second-hand smoke (SHS). These include 165,000 among children, about 60% of which occur in Africa and South-East Asia. In 2011 only four countries in the African region had comprehensive smoke-free legislation covering all public places. Given the increasing prevalence of smoking in many low income countries, preventing exposure to SHS is an urgent public health priority, particularly in sub-Sahara Africa. Objectives: The objective of this study is to obtain a reliable and nationally representative estimate of the prevalence of exposure to SHS, and to identify the major risk factors among young people in The Gambia. Settings and methods: We used two-stage cluster random sampling to select students in secondary schools throughout The Gambia, and a self-administered questionnaire to collect data on demographic characteristics and detailed indicators of exposure to SHS. Results: Of the 10,392 eligible students, 10,289 (99%; 55% girls and 44% boys, age 12-20 years) participated. The proportion of students reporting any exposure to SHS was 97.0%, (enclosed public places 59.2%, outdoor public places 61.4%, school 2l.3% and home 38.2%), with 96.4% reporting some exposure outside the home. Exposure to SHS in the home was more common in girls and among older students. Parental education, living with parents and being sent to purchase cigarettes were associated with exposure to SHS both within and outside the home. More than 50% of students supported public smoking ban in both enclosed and outdoor public places. About 35% of students were unaware of the harmful effects of exposure to SHS. Conclusions: Exposure to SHS is highly prevalent among students in the Gambia, and occurs mostly outside of the home. Interventions to reduce SHS exposure in students are urgently needed.